Stability and control effectiveness of a seamless aeroelastic wing aircraft. - Yang, Da Qing (Cranfield University, 2011)
Today’s aerospace engineers can design a much lighter aircraft than before thanks to the improved accuracy in the estimation of aerodynamic load and structural strength. But reduction of airframe material has also made the aircraft more flexible, giving rise to aeroelastic phenomena which would have profound effect on flight stability and control. From stability point of view, redistributed aerodynamic force due to wing deformation would influence the static stability of the aircraft. The structural flexibility and dynamic behaviour reduces the flight dynamic damping and influences the flight dynamic modes, which in turn could cause dynamic stability problems. From a control effectiveness perspective, control surface deflection exerts local aerodynamic force and deformation, which generally reduces intended control authority. The magnitude of control effectiveness reduction mainly depends on the structure and control surfaces design. An aircraft of special planform such as swept back wing makes the problem more complicated. This research project was motivated by the Active Aeroelastic Wing Technology (AAWT) demonstrated by the F/A-18AAW (later known as NASA X-53). The proposed research aircraft was a small flying wing type aircraft with 40 degree swept back angle and centrally mounted high swept fin. Powered by a single micro jet engine, this technology demonstrator features a Seamless Aeroelastic Wing (SAW). This study follows the AAWT approach, but extends the AAWT discrete rigid body control surfaces to spanwise continuous and chordwise hingeless control surfaces, integrated with internal actuation system. This research is aimed to achieve the stability and controllability of an aircraft with a specifically designed flexible seamless aeroelastic wing, which had control effectiveness problem. Firstly an investigation was made to mitigate the stability problems of the SAW aircraft. Then secondly, based on the SAW feature, the research proposes a systematic solution to the control effectiveness problem of this SAW aircraft. The solution would combine multidisciplinary efforts including aeroelastic tailoring, novel control surface actuation system design, distributed flight control management and active flight control algorithm. In the study, the effect of structural flexibility and dynamic behaviour of the wing on the flight dynamics has been considered. This thesis covers design, modelling, simulation and control of the SAW aircraft. The design, modelling, simulation, prototype construction and testing of the SAW were undertaken with collaboration of another PhD student and part of the work is also included in this thesis. The study has shown that the stability of the SAW aircraft can satisfy flying quality requirements with the compensation of stability augmentation system. The control effectiveness can be increased by SAW technology comparing with a conventional hinged control surface design. Flight envelope can be extended beyond control reversal speed with the aid of successfully designed gain scheduling control algorithm. The SAW aircraft shares many common aeroelastic problems with other flexible aircraft, but also has aeroelastic problems specific to its own design. If the design is changed, detailed solution would be altered accordingly, but the problem solving approach would be applicable. This research views these problems from a system level and endeavour to lead the way forward in achieving and demonstrating a systematic approach to a series of aeroelastic problems.
Keywords: Flight dynamics; structural dynamics; morphing wing; control surface actuation mechanism; aeroelastic control reversal; flying wing flight control; flying quality and stability augmentation